Environmental regulations on viral abundance in the upper South China Sea inferred from statistical models. (November 2022) - Hu, Caiqin; Li, Xiangfu; Shi, Zhen; Xu, Jie
Highlights: Generalized Boosted Model was robust for predicting viral abundance in oceans. Horizontal distribution of viruses was most likely regulated by host biomass. Vertical distribution of viruses was mediated by temperature and host biomass. Abstract: Viruses play a critical role in sustaining marine ecosystems and driving biogeochemical cycling of elements. To better understand the underlying mechanisms for environmental regulations on viral abundance (VA) and more accurately predict VA in the upper 200 m of the South China Sea (SCS), five statistical models were constructed to fit the relationship between VA and geographical coordinates and environmental factors. Generalized boosted model (GBM) was superior in modeling and predicting VA in the SCS than the other four models. Moreover, VA predicted by GBM from geographical coordinates and environmental factors was highly consistent with the observations. GBM results showed that environmental factors were more important in mediating VA than geographical coordinates. VA declined from inshore to offshore, which was more likely regulated by bacterial abundance and chlorophyll a concentration. Vertically, regulators of VA varied with the depth. VA increased with depth in the upper 25 m, likely due to a vertical decline in temperature and ultraviolet radiation that caused viral inactivation. VA declined sharply with depth from 25 to 100 m, which was possibly related to a decrease in host (bacteria and phytoplankton) biomass. A slight reduction in VA from 100 m to 150 m was indirectly mediated by temperature. The low host biomass and the lack of substrate supply were responsible for low VA below 150 m. Our findings elucidated environmental regulations on VA in the SCS horizontally and vertically, which helped to improve our understanding of interactions of environments and microbial processes in oceans.